Customers' satisfaction on internet banking services : study on conventional banks in Kota Kinabalu / Raemah Hanapi - Hanapi, Raemah (2014)
This study aims to examine the e-serv1ce quality dimensions on the level of customers' satisfaction internet banking services by Conventional Bank. Other than that, this study also to determine the greatest factors affects the customers' satisfaction. Four independent variables had been identified that affect the level of customer satisfactions. There are reliability, responsiveness, assurance, and efficiency. The dependent variable for this study is customers' satisfaction. Literature review has been used to support dependent and independent variables. One of the most popular methods for measuring the online service quality is Zeithaml et al. (2002). There are about 100 internet banking service user have been selected in the sampling tools to provide information for the study. Data were analyzing using Statistical Package for the Social Science and described by the Data Analysis Statistics and Applied Statistics (SPSS). Result showed that the customers are satisfied on internet banking service offered by conventional bank. As for reliability and efficiency become the greatest e-service quality dimensions that are affect the level of customers' satisfaction.